Muslim Women Representation in Zoya Hijab Video Advertisement: A Multimodal Analysis (NOBEL: Journal of Literature and Language Teaching, 2021)
Advertisement as a tool of marketing usually displays the best quality of products to be advertised through the best portrayal of the products and roles shown by actresses. Women's representation in media is often related to gender roles in society. Gender stereotypes often determine how men and women should behave in society. Our review of the previous research shows that there is an inconsistency in the representation of women in media and advertisements. The current research collected data from Zoya Hijab video advertisements to reveal Muslim women's representation in the advertisements. The data analysis was conducted by applying multimodal analysis using Kress and Van Leeuwen’s (2006) visual grammar and Halliday’s (1994) systemic functional linguistics. The research results show the portrayal of Muslim women in terms of physical appearance, occupation, behavior, and traits in the video advertisements